Controlled deposition and combing of DNA across lithographically defined patterns on silicon - Esmail Nazari, Zeinab; Gurevich, Leonid (Beilstein Journal of Nanotechnology, 2013)
We have developed a new procedure for efficient combing of DNA on a silicon substrate, which allows reproducible deposition and alignment of DNA molecules across lithographically defined patterns. The technique involves surface modification of Si/SiO2 substrates with a hydrophobic silane by using gas-phase deposition. Thereafter, DNA molecules are aligned by dragging the droplet on the hydrophobic substrate with a pipette tip. Using this procedure, DNA molecules were stretched to an average value of 122% of their contour length. Furthermore, we demonstrated combing of ca. 900 nm long stretches of genomic DNA across nanofabricated electrodes, which was not possible by using other available combing methods. Similar results were also obtained for DNA–peptide conjugates. We suggest this method as a simple yet reliable technique for depositing and aligning DNA and DNA derivatives across nanofabricated patterns.
Keywords: AFM; DNA molecular combing; DNA–peptide complexes; molecular electronics; surface modification